2017
DOI: 10.1039/c7ra03784h
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-template technology inducing and regulating cationic microblocks in CPAM: characterization, mechanism and sludge flocculation performance

Abstract: In this study, the ultrasonic-template polymerization technique (UTPT) was used to generate and regulate the distribution of cationic microblocks in a polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…18 If the anionic units orderly distributes in the polymer chain of APAM to form the anionic microblock structure, the negative charge of the anionic group becomes more centralized and will neutralize the positive charged particles completely, thus increasing the charge neutralization ability. 19 Meanwhile, the strong repulsive force between anionic microblocks are advantageous for the stretch and extension of the polymer chain, and therefore the bridging ability of the polymer is improved. 20 Now, the most critical issue is to search for a new approach to prepare the novel APAM with microblock structure, whereas it is incapable for traditional synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…18 If the anionic units orderly distributes in the polymer chain of APAM to form the anionic microblock structure, the negative charge of the anionic group becomes more centralized and will neutralize the positive charged particles completely, thus increasing the charge neutralization ability. 19 Meanwhile, the strong repulsive force between anionic microblocks are advantageous for the stretch and extension of the polymer chain, and therefore the bridging ability of the polymer is improved. 20 Now, the most critical issue is to search for a new approach to prepare the novel APAM with microblock structure, whereas it is incapable for traditional synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…The originally ordered structure of PAD was destroyed by the grafting of hydrophobic AODBAC, thus leading to a porous structure with a prodigious surface area which was favorable for the improving of flocculation and water solubility ability of PADA. Besides, Figure 5(b) also showed a linear correlation of the natural logarithms of the perimeter ( ) and the area ( ), indicating that the fractal dimension of the polymer surface could be calculated using Image-Pro Plus 6.0 software [22,23]. The results showed that the fractal dimensions of PAD and PADA were 1.236 and 1.403, respectively.…”
Section: Sem Of Polymersmentioning
confidence: 77%
“…PAD and PADA showed the following similar resonance peaks. The resonance peaks for the protons of −CH 2 − (a) and −CH− (b) at backbone of the polymer were observed at 1.63 ppm and 2.19 ppm, respectively [22]. The resonance peaks for the protons of −O−CH 2 − (c) were observed at 4.61 ppm.…”
Section: 12mentioning
confidence: 79%
See 1 more Smart Citation
“…The formed positively charged polymer electrolyte after dissolved in water can give full play to its electrical neutralization and adsorption bridging effect, so as to effectively flocculate compounds and colloidal substances in wastewater, so that these substances are easier to separate from water [7,8]. Because CPAM has the multiple function of turbidity removal, decolorization, adsorption, filtration and purification, it has been widely used in environment field, especially in sludge dewatering [9,10].…”
Section: Introductionmentioning
confidence: 99%